Stereoselective synthesis of exocyclic allenes by double hydride reduction of 3-alkynyl-2-cycloalkenones. Issue 40 (6th October 2016) - Gubbels, Matthew A.; Hulce, Martin; Kum, John M.; Urick, Andrew K.; Villa, Eric M.
Abstract: Exocyclic allene natural products and pharmaceutical agents are rare but interesting compounds: Fucoxanthin, grasshopper ketone, and analogues of prostacyclins, cephalosporins, antithrombic agents and sterol biosynthesis inhibitors are representative. Syntheses of exocyclic allenes commonly rely on extended conjugate additions to e.g., alk-2-en-4-ynones, syn SN 2′-like additions to alkynyl oxiranes, and substitution reactions such as electrophilic substitutions of propargylic silanes. We report that the reaction of 3-alkynyl-2-cycloalkenones with 2 equiv of various hydridoaluminates but not hydridoborates proceeds via diastereoselective 1, 4-reduction of a vinylogously propargylic intermediate alcoholate to provide exocyclic allenes as major products. Isomeric 3-alkynylcycloalkanols also are observed. Graphical abstract: